KESEPIAN PADA LANJUT USIA: STUDI TENTANG BENTUK, FAKTOR PENCETUS DAN STRATEGI KOPING - Septiningsih, Dyah Siti; Na'imah, Tri (Faculty of Psychology, Diponegoro University, 2012)
This study aimed to: 1) explore forms of loneliness experienced by the elderly, 2) identify factors that triggered the loneliness in the elderly, 3) explore the coping strategies used by the elderly in overcoming loneliness. Study sites were in East Purwokerto, and South Purwokerto. There were eight primary informants for this research. Four participants were in East Purwokerto and the other four were in South Purwokerto. In addition, there were secondary informants consisted of children and neighbors of the primary informants. Data were collected through in-depth interviews and observation. Data were processed by an interactive analysis model. This study found that all the elderly experienced loneliness mixture. Six participants experienced emotional anxiety and situational anxiety and two participants experienced emotional anxiety and social anxiety. Factors related to the emergence of loneliness in 8 participants were: 1) loss of a figure who could provide them with attention, 2) loss of social integration which was related both to the absence of friends whom they could communicate with and to their reluctance to communicate, 3) the feeling of being left by the people whom they loved. All participants developed emotional coping to overcome the loneliness in different methods, namely three participants used self-control method and five participants used self-control and positive reappraisal.Key words: lonely, elderly, coping strategies